Proceedings of the 3rd International Electronic Conference on Environmental Research and Public Health —Public Health Issues In 2021
DOI: 10.3390/ecerph-3-09029
|View full text |Cite
|
Sign up to set email alerts
|

The influence of manual therapy on biometric parameters in patients with improper body weight.

Abstract: In recent years, there have been only a few studies showing an improvement of the lymphatic system function in patients with abnormal body weight after the use of manual lymphatic drainage (MLD). The aim of the study was to assess the effectiveness of using MLD of the abdominal cavity as one of the forms of therapy for lymphatic system dysfunction in people with abnormal body weight. Material and methods: The study presents the therapy of two women aged 30 to 59. They underwent 10 treatments of manual lymphati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…There are also reports suggesting a positive effect of MLD on the treatment of women with infertility [180], as well as people with rosacea accompanied by chronic lymphoedema of the face [181]. The search for therapeutic interventions aimed at supporting the treatment of obesity, including the reduction of comorbid chronic inflammation, has been the subject of the work only of a few researchers, including our team [101,[182][183][184][185]. For example, a study by Arngrim et al, investigated subcutaneous adipose tissue lymphatic drainage of macromolecules in lean and obese subjects and, furthermore, evaluated whether adipose tissue lymphatic drainage may change in parallel with adipose tissue blood flow [182].…”
Section: Manual Lymphatic Drainage As a New Therapeutic Option Supporting The Functions Of The Lymphatic System In The Course Of Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…There are also reports suggesting a positive effect of MLD on the treatment of women with infertility [180], as well as people with rosacea accompanied by chronic lymphoedema of the face [181]. The search for therapeutic interventions aimed at supporting the treatment of obesity, including the reduction of comorbid chronic inflammation, has been the subject of the work only of a few researchers, including our team [101,[182][183][184][185]. For example, a study by Arngrim et al, investigated subcutaneous adipose tissue lymphatic drainage of macromolecules in lean and obese subjects and, furthermore, evaluated whether adipose tissue lymphatic drainage may change in parallel with adipose tissue blood flow [182].…”
Section: Manual Lymphatic Drainage As a New Therapeutic Option Supporting The Functions Of The Lymphatic System In The Course Of Obesitymentioning
confidence: 99%
“…Nevertheless, the best results were obtained with MLD [183]. Our initial research indicated the potential benefits of the application of MLD in improving biochemical parameters, including a reduction in the inflammation and improvement in the quality of life in patients with overweight and obesity class 2 [184,185]. However, further studies on a larger number of patients, both overweight and obese, are needed to thoroughly investigate the effectiveness of manual lymphatic drainage in the course of obesity.…”
Section: Manual Lymphatic Drainage As a New Therapeutic Option Supporting The Functions Of The Lymphatic System In The Course Of Obesitymentioning
confidence: 99%